MARKET SEEKING & STRATEGY DEVELOPMENT IN WEST AND NORTH AFRICAN COUNTRIES: A TURKISH FAMILY BUSINESS EXPERIENCE - Souleymane Bindjo; Esra Dil (Akademik İncelemeler Dergisi)
This study aims to reveal the situation of small-scale family businesses that are looking for a market in Western and North African countries and want to realize their growth strategies in this region, and to develop solutions for their growth problems. For this purpose, the market development stages of the selected ABC Company were evaluated within the scope of action research. One of the researchers worked in the company within the scope of UPEP (Üniversiteden Pazar Elçiliğine Projesi -From University to the Market Ambassador Project) in the field to conduct action research, while the other researcher supervised the process academically. Inherent in action research is an approach to find a solution to the problem of the unit that is the subject of the research. The researchers analyzed the market search and development strategies of the company subject to the research and seek solutions for their growth problems. As a result of the research, it is concluded that the example ABC Company, which wants to be effective in these markets, will follow the stage model while opening up to international markets, and will be more effective in terms of penetration into the market. The literature that this result is suitable for small-scale family businesses that are in search of similar support has been supported.